Bahasa Isyarat dan Antusiasme Bekerja Karyawan Disabilitas di Sunyi Coffee - Natania, Fiona; Loisa, Riris (Koneksi, 2023)
The lack of job opportunities due to the wrong stigma in the world of disabilities is a problem that needs to be resolved. Therefore, socially-oriented businesses that are open as a forum for employees with disabilities have emerged. Good business communication has great power over a socially oriented business and the enthusiasm of employees working in it. Sunyi Coffee is a coffee shop where all employees are persons with disabilities with different impairments, the majority are deaf and mute. The purpose of this study is to describe how socially oriented business communication builds enthusiasm for the work of employees with disabilities and what the obstacles experienced in efforts to develop an enthusiasm for the work of employees with disabilities in socially oriented business communication and what the solutions are. This study uses the theories and concepts of business communication, non-verbal communication, socially oriented business, employees with disabilities, and employee enthusiasm for work. Using a qualitative approach and case study research method with data acquisition through interviews with Sunyi Group founders, Sunyi Coffee disabled employees, observation, documentation, and literature study. This study also uses coding as a data collection and analysis technique and source triangulation as a data validation technique. The results obtained from this study reveal that Sunyi Coffee's socially oriented business communication process needs to adapt and innovate, provide accessibility, and special tools, modify the environment, and achieve the desired changes in employees through a family and professional approach that is carried out using non-verbal communication. Sign language is the main language for business communication processes in Sunyi Coffee, so enthusiasm for working with employees with disabilities is built. Minimnya lapangan pekerjaan karena adanya stigma yang salah dalam dunia disabilitas merupakan masalah yang perlu diselesaikan. Maka dari itu, bisnis berorientasi sosial yang terbuka sebagai wadah bagi para karyawan disabilitas bermunculan. Komunikasi bisnis yang baik memiliki kekuatan yang besar terhadap suatu bisnis berorientasi sosial dan antusiasme bekerja karyawan di dalamnya. Sunyi Coffee merupakan sebuah kedai kopi yang seluruh karyawannya merupakan penyandang disabilitas dengan gangguan yang berbeda-beda, mayoritas tunarungu dan tunawicara. Tujuan penelitian ini adalah untuk menggambarkan bagaimana komunikasi bisnis berorientasi sosial dalam membangun antusiasme bekerja karyawan disabilitas dan apa hambatan yang dialami dalam upaya pembangunan antusiasme bekerja karyawan disabilitas dalam komunikasi bisnis berorientasi sosial serta bagaimana solusinya. Dalam penelitian ini menggunakan teori dan konsep komunikasi bisnis, komunikasi non-verbal, bisnis berorientasi sosial, karyawan penyandang disabilitas, dan antusiasme bekerja karyawan. Menggunakan pendekatan kualitatif dan metode penelitian studi kasus dengan perolehan data melalui wawancara dengan founder Sunyi Group, karyawan disabilitas Sunyi Coffee, observasi, dokumentasi dan studi pustaka. Penelitian ini juga menggunakan coding sebagai teknik pengumpulan dan analisis data serta triangulasi sumber sebagai teknik keabsahan data. Hasil yang diperoleh dari penelitian ini mengungkapkan bahwa proses komunikasi bisnis berorientasi sosial Sunyi Coffee perlu beradaptasi dan berinovasi, menyediakan aksesibilitas, alat bantu khusus, modifikasi lingkungan, dan mencapai perubahan yang diinginkan pada karyawan melalui pendekatan secara kekeluargaan dan professional yang dilakukan menggunakan komunikasi non-verbal bahasa isyarat sebagai bahasa utama proses komunikasi bisnis dalam Sunyi Coffee sehingga terbangun antusiasme bekerja pada karyawan penyandang disabilitas.